Interface Manipulation to Improve Plasmon‐Coupled Photoelectrochemical Water Splitting on α‐Fe2O3 Photoanodes. Issue 1 (23rd November 2017) - Xu, Zhe; Fan, Zhongwen; Shi, Zhan; Li, Mengyu; Feng, Jianyong; Pei, Lang; Zhou, Chenguang; Zhou, Junkang; Yang, Lingxia; Li, Wenchao; Xu, Guangzhou; Yan, Shicheng; et al.
Abstract: The plasmon resonance effect of metal nanoparticles (NPs) offers a promising route to improve the solar energy conversion efficiency of semiconductors. In this study, it is revealed that hot electrons generated by the plasmon resonance effect of Au NPs tend to inject into the surface states instead of the conduction band of Fe2 O3 photoanodes, and then severe surface recombination occurs. Such an electron‐transfer process seems to be independent of external applied potentials, but is sensitive to metal–semiconductor interface properties. Passivating the surface states of Fe2 O3 with a noncatalytic Al2 O3 layer can construct an effective resonant energy‐transfer interface between Ti‐doped Fe2 O3 (Ti‐Fe2 O3 ) and Au NPs. In such a Ti‐Fe2 O3 /Al2 O3 /Au electrode configuration, the enhanced photoelectrochemical (PEC) water‐splitting performance can be attributed to the following two factors: 1) in the non‐light‐responsive wavelength range of Au NPs, both the relaxing Fermi pinning effect of the Al2 O3 passivation layer and the higher work function of Au enlarge band bending; thus promoting the charge separation; and 2) in the light‐responsive wavelength range of Au NPs, the effective resonant energy transfer contributes to light harvesting and conversion. The interface manipulation proposed herein may provide a new route to design efficient plasmonic PEC devices for energy conversion. Abstract : Hot to trot ! The plasmon resonance effect of metal nanoparticles (NPs) offers a promising route to improve the solar energy conversion efficiency of semiconductors. Hot electrons generated by the plasmon resonance effect of gold NPs, however, inject into the surface states, instead of the conduction band of Fe2 O3 photoanodes, so surface recombination occurs. The surface of Fe2 O3 can be passivated through modifying inert oxides before loading gold NPs for plasmon‐enhanced photoelectrochemical water splitting.